P71 A model to improve performance of current category 9 UK listing criteria: early liver graft dysfunction. A single centre cohort. (6th September 2011) - Al-Freah, M A B; Dionigi, E; McPhail, M J W; Foxton, M; Auzinger, G; Rela, M; Heaton, N D; O'Grady, J G; Heneghan, M A; Bernal, W; Wendon, J A
Abstract : Introduction: Current super urgent criteria for listing for early liver graft dysfunction (ELGD) in the UK (category 9, C9C) is defined as fulfilling 2 out of 4 of the following criteria within 7 days post liver transplant (LT): AST >10 000IU/l, INR >3, Lactate >3 mmol/l and absence of bile production. We demonstrated that these criteria have critically low sensitivity in predicting early post LT death or need for re-LT (Al-Freah, et al. Hepatology 2009;50 Suppl 4:A148). Aim: To develop an improved predictive model for early re-LT or death using early post-LT clinical parameters. Method: Retrospective study of all patients transplanted at our centre 1 January 2000 to 31 December 2008. Daily clinical and laboratory parameters for the first 7 days post LT were reviewed. These included AST, bilirubin, INR, lactate, vasopressor requirement and/or haemofiltration. Results: Over the study period, 1286 patients underwent first LT at our centre. Patients excluded (28) because of re-LT for hepatic artery thrombosis (22), died on table (5) and one re-LT because of donor cancer. We analysed data on 1258 patients (median age 51 (16–74) years (16–74), 60% male). The most common aetiology was viral hepatitis in 303 patients (24%) and alcohol related liver disease in 227 patients (18%); 181 patients (14.4%) with hepatocellular carcinoma. Median MELD score was 16 (6–40). Death or re-LT rate at 3 months was 9.9% (124). Only 27 (2.1%) fulfilled C9C at 3 months: 17 (63%) of those died or had re-LT within 3 months (p<0.001). C9C had sensitivity of 14% (9.8–17%), specificity 99% (98–99%), positive likelihood ratio (LR+) 15.533 (7.41–32.73) and negative likelihood ration (LR−) 0.87 (0.83–0.91). Abstract P71 table 1 shows the univariate and multivariate analyses of predictors of 3 months liver-related death or re-LT using Cox regression hazard method. Accordingly, we generated a model comprises any 1 of the following 5 to predict ELGD and death or re-LT: vasopressor requirement at day D7, D1 lactate >3 mmol/l, D7 AST >500 IU/l and D7 bilirubin >100 μmol/l. Those scored 1, 2, 3, 4 or 5 points had OR of risk of death/re-LT within 3 months of 1.26 (0.897–1.766, p=0.184), 1.345 (0.8817–2.051, p=0.171), 2.811 (1.669–4.732, p=0.0001), 15.561 (7.425–32.611, p<0.0001) and 36.509 (13.188–101.074, p<0.0001), respectively. 85 of 124 patients who had a 3 month liver related outcome met this criterion compared to 16 who met C9C. This gave sensitivity 68% (58–77%), specificity 67% (64–70%), LR+ 2.08 (1.77–2.45) and LR− 0.48 (0.36–0.63). Conclusion: The new model is simple to use and significantly improved the sensitivity of detection of severe ELGD. Validation in another cohort of LT patients is warranted.